Optimising Elite Athlete Stress Regulation via Systematic Reflections of Stressor Events - Murdoch, Elizabeth M. (Curtin University, 2024)
The overarching goals of this research were to develop, implement, and evaluate a self-reflection intervention for elite-level athletes to build resilient capacities. These goals where accomplished over four phases via two systematic reviews and meta-analyses of the literature as well as two pilot randomised controlled trials.